Acute Toxicity Test of Jernang Resin Extract (Daemonorops Draco Willd.) on Male White Rats Sprague Dawley Strain - Lavlinesia; Mursyid; Fidia Yunita (Department of Technology of Agricultural product (THP) Jambi University, 2019)
Keywords— Jernang resin extract; white rats; acute toxicity